Frugivory by birds on Miconia albicans (MELASTOMATACEAE), in a fragment of cerrado in São Carlos, southeastern Brazil - Allenspach,N. (2012)
The avian guild that consumes Miconia albicans (Melastomataceae) fruits and its phenophases were studied in a fragment of cerrado vegetation located in southeastern Brazil. The fruiting period ocurred between October and January, coinciding with the wet season. Nineteen bird species, mainly of generalistic diets, were registered consuming fruits in 96 observational hours. Species of the families Emberizidae, Thraupidae and Tyrannidae showed the largest number of visits, while those of the families Mimidae and Columbidae, with higher body mass, were responsible for a considerable number of consumed fruits. A correlation was found between body mass and average fruit consumption per visit. Tree height was a relevant factor for bird attraction. Results suggest that M. albicans may be useful in the recovery of degraded areas.